Base Nacional Comum Curricular: impactos na organização curricular de uma unidade federal de educação infantil - Weber, Karine (2022)
The National Common Curricular Base (BNCC) allows discussions and reflections on different teaching fields, such as early childhood education. This dissertation will discuss the (re)construction of the political-pedagogical project (PPP) of an early childhood education unit located in a public institution of higher education, which, in its pedagogical practices, develops a new look at early childhood education. These practices enable new ways of organizing experiences, as well as allows the transformations that take place within the classroom and in school planning. This research aims to analyze the repercussions of the guidelines proposed by the BNCC for early childhood education in the curricular organization of the Ipê Amarelo Child Education Unit (UEIIA). The theoretical support of the research was the specific legislation for early childhood education and the contribution of studies carried by Kishimoto (2016), Kramer (2012), Barbosa (2016), Fochi (2018), among others. The research is of a qualitative nature, carried out in two stages: an analysis of the PPP and, subsequently, data collection through semi-structured interviews or an online questionnaire, due to the covid-19 pandemic. It was possible to understand the movement that the UEIIA carried out for the (re)construction of the PPP, which observed how the limitations and potential of the BNCC were adapted to a proposal that values the role of children from an interpretation of the BNCC that open possibilities of action without showing forms of implementation that restrict the principles and specificities of early childhood education.